Long-term Outcomes and Risk Factors After Adult Living Donor Liver Transplantation. Issue 9 (September 2018) - Imai, Daisuke; Yoshizumi, Tomoharu; Sakata, Kazuhito; Ikegami, Toru; Itoh, Shinji; Harada, Noboru; Motomura, Takashi; Toshima, Takeo; Mano, Yohei; Soejima, Yuji; Maehara, Yoshihiko
Abstract : Background: Although risk factors for the long-term mortality of liver transplantation are well described, there is a lack of detailed study regarding these factors for adult living donor liver transplantation (LDLT). Methods: We retrospectively analyzed 528 adult LDLT recipients in our hospital. The risk factors were analyzed for overall deaths more than 5 years post-LDLT. Results: Over the 20-year follow-up, 137 patients died. Patient survival at 1, 3, 5, and 10 years post-LDLT was 87.8%, 81.8%, 79.4%, and 72.8%, respectively. The independent risk factors for more than 5 years post-LDLT overall death were hepatocellular carcinoma recurrence (hazard ratio [HR], 38.9; P < 0.001), lymphoid de novo malignancy (HR, 47.2; P = 0.001), primary sclerosing cholangitis as primary diagnosis (HR, 11.5; P < 0.001), chronic rejection (HR, 6.93; P = 0.006), acute rejection (HR, 2.96; P = 0.017), and bile duct stenosis (HR, 2.30; P = 0.045). Conclusions: Not only malignancies and rejection but also bile duct stenosis and primary sclerosing cholangitis had significant impacts on late period post-LDLT mortality. Abstract : In this large single-center retrospective study, the authors describe the long-term mortality and risk factors following adult living donor liver transplantation highlighting the importance of malignancies, rejection, and bile duct stenosis.